Superficial self-diffusion coefficient in Ih-ICE - Di Prinzio, Carlos Leonardo (2020)
The evolution of the grain boundary groove in a bicrystalline ice sample was studied in this work. The groove is formed by the intersection of the grain boundary with the free surface. The bicrystalline ice sample had an arbitrary misorientation and was immersed in ultra-pure silicone oil at −5°C in order to avoid evaporation processes. Photographs of the groove were taken every 17 minutes for 100 hours with an optical microscope and the evolution of the groove was determined from these images. Through this study, it was possible to measure the coefficient of surface self-diffusion of the ice at −5°C.